BLOCKCHAIN DALAM EKONOMI ISLAM - Naila Faiza, Nur; Inayah, Fadilatul (ISTISMAR, 2024)
Blockchain is currently being talked about a lot, especially architecture with cryptocurrencies. In the development of sharia finance, public enthusiasm for sharia economic practices and innovation in sharia services such as fintech has an important role. The aim behind this research is to understand the Islamic views on Blockchain. In this research, data collection was carried out using the library research method, where information was obtained through literature review from various sources such as books, journals, regulations and other scientific writings. This research uses a descriptive qualitative method approach. The development of sharia finance in various fields, including banking and non-banking, is also driven by enthusiasm for sharia economic community practices and various sharia service innovations such as fintech. The use of blockchain technology in the sharia financial sector can be realized by implementing smart contracts in sharia banking activities, optimizing zakat collection, increasing the benefits of waqf, creating halal value chains, and applying blockchain technology to retail sukuk bonds.